2016
DOI: 10.1007/s11999-015-4480-x
|View full text |Cite|
|
Sign up to set email alerts
|

Can a Conical Implant Successfully Address Complex Anatomy in Primary THA? Radiographs and Hip Scores at Early Followup

Abstract: Background Total hip arthroplasty (THA) in patients with small or abnormal proximal femoral anatomy is challenging as a result of complex anatomic deformities in the hip. It is unclear which stem is the most appropriate for these patients. One possible implant design that may help meet this need is the modified Wagner Cone prosthesis, whose design consists of monoblock cone with splines; however, to our knowledge, no clinical results have been published using this implant. Questions/purposes We evaluated the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Coxarthrosis secondary to DDH leads to pathological bony anatomy and severe biomechanical alterations around the hip joint, increasing the difficulty of THA, which remains the treatment of choice for endstage arthritis of the hip. In such an abnormal proximal femoral morphology, a stem with metaphyseal fitting flat-wedge taper or fit and fill should not be considered appropriate [9,21], while a diaphyseal engaging stem that dials in the desired amount of anteversion is desirable, owing to its capability of adaptation in small femurs, with poor metaphyseal bone quality, and possibly with previous hip surgeries. Its use should therefore minimize the risk of threatening the long-term survival of the prosthetic implant related to aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coxarthrosis secondary to DDH leads to pathological bony anatomy and severe biomechanical alterations around the hip joint, increasing the difficulty of THA, which remains the treatment of choice for endstage arthritis of the hip. In such an abnormal proximal femoral morphology, a stem with metaphyseal fitting flat-wedge taper or fit and fill should not be considered appropriate [9,21], while a diaphyseal engaging stem that dials in the desired amount of anteversion is desirable, owing to its capability of adaptation in small femurs, with poor metaphyseal bone quality, and possibly with previous hip surgeries. Its use should therefore minimize the risk of threatening the long-term survival of the prosthetic implant related to aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…The Kaplan Meier curve shows the probability of survival for the Wagner cone femoral stem along the follow-up demonstrated stability of all implants [9]. It has been shown that there are fewer implant-related complications in patients undergoing THA with a dislocated hip classified as Crowe type IV when cylindrical stems 2/3 coated were used to reconstruct a step-cut osteotomized femur compared with tapered stems with 1/3 proximal coating [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the short-term follow-up, the clinical and radiographic outcomes of the new dual-conical stem are comparable with the results reported in the literature for other conical implants in the treatment of difficult primary or Paprosky I, II, IIIA revision cases. Zhang et al 9 described the use of 49 cone stems utilised on patients whose femoral geometry precluded the use of standard-sized implants (femoral neck retroversion, excessive anteversion of the femoral neck, or small proximal femora). After a minimum of 3 years follow-up, they observed only 1 case of revision surgery as a result of late infection, with HHS that improved from 41 to 85 at last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…19 Specifically designed femoral stems such as the cementless modular implant (S-ROM; DePuy Synthes, Warsaw, IN USA) and cementless conical implant (Wagner Cone; Zimmer Biomet, Warsaw, IN, USA) were developed to provide a better fit in femoral medullary canals with anatomical deformities, and the successful application of these designs has been supported by studies with short-to long-term follow-up. [20][21][22][23][24][25][26][27][28] Nevertheless, complications such as proximal femoral fracture are still reported in patients with DDH. [20][21][22][23][24]29,30 We have found that for some patients with Crowe IV DDH in our clinical practice, it is difficult to insert any on-shelf prostheses (including the specialized designs mentioned above) into the femoral canal at a desirable position.…”
Section: Introductionmentioning
confidence: 99%